Benelux countries in Poland’s foreign policy (Economic and Political Thought, 2019)
The name Benelux is a commonly known abbreviation of the Europeanorganisation formed by three states: the Kingdom of Belgium, the Kingdomof the Netherlands and the Duchy of Luxemburg. The Benelux Union startedin 1944 as a tariff union, which was finalised by a treaty establishing theBenelux Economic Union in 1958. The new Benelux Treaty was signed on17 June 2008 in The Hague. Since then, the cooperation has been focusedon the following main areas: the internal and the economic union market,sustainable development, justice and internal affairs. The mission of Beneluxis the best possible cooperation between the member states and ensuring thewelfare of the citizens of Belgium, the Netherlands and Luxemburg.After Poland’s accession to the European Union, Polish politicians’ interestin the functioning of the Benelux states decreased although the presentdemocratic Poland’s governments use the common achievements of all itsmember states. Polish governments’ foreign policy towards the Benelux statesis at present carried out within the Visegrad Group in the V4+ (plus) format.On 19 June 2017, after 16 years’ break, the Visegrad Group and Beneluxstates’ Prime Ministers met in Warsaw. The debate on the future of theEuropean Union was the impulse to return to talks at the prime ministers’level. Actually, two issues divide the V4 and the Benelux states. The BeneluxUnion states are for the quota solution, which the V4 states oppose. Theissue of the European integration within the ‘multi-speed idea’ constitutesanother division line. As far as this is concerned, there are differences withinthe V4 but most members are against it. The Visegrad – Benelux cooperationnowadays consists in attempting to form coalition with the Benelux states inthe EU voting in order to achieve trans-regional agreements. The experienceprescribes maintaining scepticism about predicting agreements betweenthe Czech Republic, Hungary and Poland and the Netherlands, Belgium,Luxemburg and Slovakia. The meeting in Warsaw proved that the debate onthe future of the European Union to a great extent would first take place inregional groups and then formally in the EU forum.
Keywords: Benelux, Visegrad, V4+ format, Utrecht Conferences